2017
DOI: 10.11648/j.edu.20170606.14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Influence of Family Background and Cultural Capital on the Non-cognitive Skills of Children

Abstract: Abstract:The non-cognitive skills of children in family reproduction have been concerned more and more. Based on the survey of junior middle school student, we used principal component analysis to obtain the value of the index of non-cognitive skills, and further adopted the OLS method analyzing the determinants of the non-cognitive skills. It is shown that family income, parental occupations and education, participating in parent-child cultural activities, family collection of books, the grade of child, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Lee and Zhou, 2017). The results also fit comfortably with studies of the effects that family background (Fletcher and Wolfe, 2016; Khanam and Nghiem, 2016; Luo et al., 2017) and parental involvement (Bornstein et al., 2003; Glick et al., 2012; Ngai, 2015) have on child development, while revealing the mediating role of parenting practice in the relationship between parental migrant status and non-cognitive abilities in the Hong Kong context.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Lee and Zhou, 2017). The results also fit comfortably with studies of the effects that family background (Fletcher and Wolfe, 2016; Khanam and Nghiem, 2016; Luo et al., 2017) and parental involvement (Bornstein et al., 2003; Glick et al., 2012; Ngai, 2015) have on child development, while revealing the mediating role of parenting practice in the relationship between parental migrant status and non-cognitive abilities in the Hong Kong context.…”
Section: Resultssupporting
confidence: 85%
“…In the USA, for example, much of the educational success of Asian immigrants’ children can be explained by their favorable family background (Kao, 1995), while the low educational achievement of Mexican immigrants’ children can mostly be attributed to family socioeconomic status (Warren, 1996). Furthermore, family background plays a significant role in children’s non-cognitive development (Fletcher and Wolfe, 2016; Khanam and Nghiem, 2016; Luo et al., 2017).…”
Section: Family Background Parenting Practices and Children Of Chinmentioning
confidence: 99%
“…Most studies showed that family socioeconomic status (SES) and cultural capital had a significant impact on children's noncognitive abilities (Peter, 2016;Anger and Schnitzlein, 2017;Luo and Guan, 2017;Du et al, 2018;Yao and Ye, 2018). To be specific, the enhancement of family SES and family cultural capital could improve children's noncognitive abilities Luo and Guan, 2017;Du et al, 2018;Yao and Ye, 2018). On the contrary, lower SES, such as mother's unemployment was not conducive to the improvement of children's noncognitive abilities (Peter, 2016).…”
Section: The Determinants Of Children's Noncognitive Abilitiesmentioning
confidence: 99%
“…Recent researches paid more attention to the relationship of family background and children's noncognitive abilities and discussed the impact of family socioeconomic status and cultural capital on children's noncognitive abilities (Peter, 2016; Anger and Schnitzlein, 2017; Li and Zhao, 2017; Li et al , 2017; Luo and Guan, 2017; Du et al , 2018; Yao and Ye, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation